Developing literacy in the multiple intelligences classroom (California : SkyLight Professional Development, 1999)
This video views about theory of multiple intelligencies provides the underpinning for this discussion of integrated language art and literacy development
Executive producer, Ela Aktay
Keywords: Effective teaching